Stock Market Risk and Return: An Equilibrium Approach - Whitelaw, Robert F. (Review of Financial Studies, 2000)
Recent empirical evidence suggests that expected stock returns are weakly, or even negatively, related to the volatility of stock returns at the market level, and that this relation varies substantially over time. This evidence contradicts the apparently reliable intuition that risk and return are positively related and that stock market volatility is a good proxy for risk. This paper investigates the relation between volatility and expected returns in a general equilibrium, exchange economy. A relatively simple model, estimated using aggregate consumption data, is able to duplicate the salient features of the observed expected return/volatility relation. The key features of the model are the existence of two regimes with different consumption growth processes and time-varying correlations between stock returns and the marginal rate of substitution; thus inducing variability in the short-run relation between expected returns and volatility and a weakening of the long-run relation. These results highlight the perils of relying on intuition from static models. They also have important implications for the empirical modeling of returns.